Three-dimensional finite element analysis of stress distribution on short implants with different bone conditions and osseointegration rates - Yunhe Yang; Yuchen Liu; Xi Yuan; Mingfa Ren; Xiaodong Chen; Lailong Luo; Lang Zheng; Yang Liu (BMC, 2023)
Abstract Objective This experiment aimed to investigate the effects of bone conditions and osseointegration rates on the stress distribution of short implants using finite element analysis and also to provide some reference for the application of short implants from a biomechanical prospect. Materials and methods Anisotropic jaw bone models with three bone conditions and 4.1 × 6 mm implant models were created, and four osseointegration rates were simulated. Stress and strain for the implants and jaws were calculated during vertical or oblique loading. Results The cortical bone area around the implant neck was most stressed. The maximum von Mises stress in cortical bone increased with bone deterioration and osseointegration rate, with maximum values of 144.32 MPa and 203.94 MPa for vertical and inclined loading, respectively. The osseointegration rate had the greatest effect on the maximum principal stress in cortical bone of type III bone, with its value increasing by 63.8% at a 100% osseointegration rate versus a 25% osseointegration rate. The maximum and minimum principal stresses under inclined load are 1.3 ~ 1.7 and 1.4 ~ 1.8 times, respectively, those under vertical load. The stress on the jaw bone did not exceed the threshold when the osseointegration rate was ≥ 50% for Type II and 100% for Type III. High strain zones are found in cancellous bone, and the maximum strain increases as the bone condition deteriorate and the rate of osseointegration decreases. Conclusions The maximum stress in the jaw bone increases as the bone condition deteriorates and the osseointegration rate increases. Increased osseointegration rate reduces cancellous bone strain and improves implant stability without exceeding the yield strength of the cortical bone. When the bone condition is good, and the osseointegration ratio is relatively high, 6 mm short implants can be used. In clinical practice, incline loading is an unfavorable loading condition, and axial loading should be used as much as possible.